19-Oxo-5-α-Carda-14,20(22)-Dienolide-O-β-D-Glucopyranoside from Millettia ovalifolia Roots - Bose, Chandana; Chakraborty, Ajita (Asian Journal of Chemistry, 2010)
The roots of Millettia ovalifolia, commonly known as Gauj belongs to n.o. Leguminosae. The roots of this plant are reported to be poisonous. The ethyl acetate soluble fraction of the concentrated ethyl alcohol soluble part of its roots when subjected to column chromatography yielded a light yellow coloured compound, mf. C29H40O9, m.p. 263-64°C, [α]D18 = 36.7° (CH3OH), and M+ = 370, which on various chemical degradations, colour reactions and spectral analysis was identified as 19-oxo-5-α-carda-14,20 (22)-dienolide-3-O-β-D-glucopyranoside [compound C-1]..